Endothelin-1/Nitric Oxide Ratio as a Predictive Factor of Response to Therapy With Terlipressin and Albumin in Patients With Type-1 Hepatorenal Syndrome - Abdel-Razik, Ahmed; Mousa, Nasser; Abdelsalam, Mostafa; Abdelwahab, Ahmed; Tawfik, Mona; Tawfik, Ahmed M.; Hasan, Ahmad S.; Elhelaly, Rania; El-Wakeel, Niveen; Eldars, Waleed (Frontiers in Pharmacology, 2020)
Background and Purpose: Predictors of response to type-1 hepatorenal syndrome (HRS) therapy are urgently needed. This study’s purpose is to evaluate the proposed predictors in these patients. Methods: 42 type-1 HRS patients with cirrhosis were treated with albumin and terlipressin. Clinical, biochemical, and demographic parameters taken at the onset of therapy and changes in endothelin-1/nitric oxide (ET-1/NO) ratio during therapy were analyzed to check their predictive value. Results: Response to treatment (serum creatinine level <1.5 mg/dL at the end of therapy) was shown in 20 patients (48%). Independent predictive variables of response to therapy were early reduction of ET-1/NO ratio ≥0.15 at day 3 of therapy and serum bilirubin baseline <8 mg/dL (area under the receiver operating characteristic curve, 0.751; P<0.001; specificity, 55%; sensitivity, 85%). Response rates in patients with serum bilirubin level <8 mg/dL and ≥8 mg/dL were 63% and 20%, respectively (P=0.008). The corresponding values in patients with an early reduction of ET-1/NO ratio ≥0.15 and <0.15 on day 3 were 85% and 13.6%, respectively (P<0.001). Conclusions: Early reduction of ET-1/NO ratio and lower serum bilirubin baseline can predict response to type-1 HRS therapy with albumin and terlipressin. Alternative therapy should be investigated for nonresponder type-1 HRS patients.